Culturally responsive research ethics: how the socio-ethical norms of Arr-nar/Kreng-jai inform research participation at the Thai-Myanmar border - Khirikoekkong, N; Asarath, S-A; Nosten, S; Hanboonkunupakarn, B; Jatupornpimol, N; Roest, J; Parker, M; Nosten, F; McGready, R; Cheah, PY; Kelley, M (Public Library of Science, 2023)
Despite advances, international research ethics guidelines still tend to consist of high-level ethical principles reflecting residual influence from North American and European traditions of ethics. Local ethics committees and community advisory boards can offer more culturally-sensitive approaches to training but most institutions lack substantive practical ethics guidance to engage rich moral understandings in day-to-day research practice in diverse cultural contexts. To address this gap, we conducted an international series of qualitative research ethics case studies, linked prospectively to active research programs in diverse settings. Here, we share findings from two case studies with a research team working on malaria and hepatitis B prevention with pregnant women in clinics serving migrants along the Thai-Myanmar border. In this sociocultural ethical analysis, we consider how core ethical requirements of voluntary participation, provision of fair benefits, and understandings of research risks and burdens are shaped, enriched, and in some instances challenged, by deep-seated and widespread Burmese, Karen and Thai cultural norms known as Arr-nar (in Burmese and Karen) or Kreng-jai (in Thai), encompassing multiple meanings including consideration for others and graciousness. We offer a model illustrating how one might map ethically significant sociocultural influences across the research practice pathway and close with lessons for developing a more culturally responsive research ethics practice in other international settings.